Upaya Perbaikan Sistem Politik Sebagai Strategi Pengurangan Silpa Pada Pemerintah Kota Yogyakarta - Lail, Ramadhani Nurullah Addaru; Trigopala, Komang Yuda (Media Hukum Indonesia (MHI), 2025)
The remaining budget surplus or Silpa is a fund that is not used up in one budget period. This remaining budget occurs when the realization of an activity budget that has been planned exceeds the budget previously set in the project activity. The political system is power that is obtained by way of organization and is also exercised within a country including certain institutions. In previous studies it was said that the regional government of the City of Yogyakarta experienced problems in terms of budget planning, namely an increase in the remaining excess budget spending caused by the political system. Therefore, this study aims to analyze the improvement of the political system as a strategy for reducing Silpa in the Yogyakarta city government. The method used in this research is a qualitative research approach, namely a multi-case study. Based on the method used, it was found that there were still some defects in the implementation of the Yogyakarta City Regional Government political system which caused an increase in Silpa, so it is necessary to improve the political system used to reduce the occurrence of Silpa.